COMPARATIVE ANALYSIS OF THE MINERAL AND CHEMICAL COMPOSITIONS OF BLACK SMOKER SMOKE AT THE TAG AND BROKEN SPUR HYDROTHERMAL FIELDS, MID-ATLANTIC RIDGE - Rusakov V.Yu. (My University, 2007)
The paper presents newly obtained data on the fluxes of hydrothermal-sedimentary material collected with sedimentation traps within 3 m from the bottoms of black smokers at the TAG and Broken Spur hydrothermal fields and reports the results of comparative analysis of the mineralogical and chemical compositions of this material. The sedimentary material deposited near the vent was determined to account to approximately 3% of the overall mass of the orebody. The results demonstrate that, in both cases, the trap material is characterized by high contents of ore components and ore-forming chemical elements (Fe, Cu, Zn, and Co), and Se, As, Sb, Ba, and P compared to tholeiitic basalts from which these elements are leached. However, the material of a more "mature" (having an age of 40-50 ka) hydrothermal spring at the TAG field contains 40% Fe hydroxides, in contrast to the material of a spring at the Broken Spur field (age <1000 yr) whose material is dominated by sulfides (72%) and contains much pyrrhotite. These springs also show principal differences between the enrichment coefficients for Se (by a factor of 4.8), As (3), Ca (4.1), and Si (5.2). These differences are thought to reflect various evolutionary stages of the circulating hydrothermal systems. © Pleiades Publishing, Ltd. 2007.